A Review on Sentiment Analysis in Arabic Using Document Level - Awajan, Ibrahim; Mohamad, Mumtazimah (International Journal of Engineering and Technology, 2018)
With the rapid increase of web contents and the spread of social media and microblogs such as Twitter and etc.., the focus on the sentiment analysis (SA) is deeply being studied. The research on Arabic sentiment analysis is progressing very slow in compared to English sentiment analysis. The former has recently attracted a considerable concentration of researchers. In this respect, this paper aims to present a brief review of some major works that have addressed the document-level sentiment analysis in Arabic. This review includes research and studies published during the period of 2011-2017 for different approaches of document-level sentiment analysis.Â Â Â